No dynamic changes in plasma ACE2 activity in patients with acute coronary syndrome. (14th October 2021) - Hamilton, G; Patel, S K; Azraai, M; Burrell, L M
Abstract: Background: Angiotensin converting enzyme 2 (ACE2) is expressed in the human myocardium and blood vessels and degrades the vasoconstrictor peptide angiotensin (Ang) II. Plasma ACE2 activity is elevated in patients with cardiovascular disease (CVD) and is a predictor of major adverse cardiovascular events (MACE) in obstructive coronary artery disease. However, it is unknown whether acute coronary syndrome (ACS) causes dynamic changes in plasma ACE2 activity. Purpose: We investigated dynamic changes in serial troponin-T and plasma ACE2 activity in patients presenting with ACS who underwent invasive coronary angiography (ICA). Methods: Consecutive patients admitted with ACS from October-November 2019 were screened. Those meeting the Fourth Universal Definition of Myocardial Infarction who had both ICA and serial troponin-T testing were included. The study was approved by the hospitals Human Research Ethics Committee. All patients had routine plasma samples taken over 3 time-points for measurement of troponin-T; the same sample was used to measure plasma ACE2 activity. Catalytic ACE2 activity was measured using a validated, sensitive quenched fluorescent substrate-based assay. Serial median troponin and ACE2 activity levels were analysed using the Friedman test for repeated measures. Results: Forty-nine patients were included. The mean age of participants was 63.9±11.0 years, and 36 (74%) patients were male. Overall, 16 (36%) patients presented with ST-elevation myocardial infarction (STEMI) and 29 (74%) with non-ST-elevation myocardial infarction (NSTEMI). Twenty-nine (59%) patients had a history of hypertension and 14 (29%) a history of ischaemic heart disease; 13 (27%) with priorMI, 11 (22%) had previous PCI and 2 (4%) had prior coronary artery bypass grafting. Over the 3 time points, there was a clear rise in median troponin-T levels representing myocardial injury (p<0.001), with no change in median plasma ACE2 activity (p=0.23, table 1). There was no difference in median ACE2 activity in those presenting with STEMI vs. NSTEMI (6.9 [2.1–9.5] vs. 6.0 [1.8–12.1], p=0.87), nor in those who underwent PCI to a culprit lesion compared to those who did not have a culprit lesion stented (5.8 [0.9–10.5] vs. 7.3 [2.8–14.9], p=0.37). Conclusions: Patients with ACS had higher plasma ACE2 levels compared to levels previously reported in healthy controls. There were no dynamic changes in ACE2 activity in the setting of ACS, despite a significant rise in troponin-T. These results suggest that plasma ACE2 levels reflect underlying endothelial dysfunction rather than acute myocardial injury or infarction. Studies are now underway to assess if plasma ACE2 activity in ACS predicts MACE. Funding Acknowledgement: Type of funding sources: None.